2001
DOI: 10.1016/s0921-4526(01)00631-7
|View full text |Cite
|
Sign up to set email alerts
|

Doping dependence of the barrier height and ideality factor of Au/n-GaAs Schottky diodes at low temperatures

Abstract: The barrier height and ideality factor of Au/n-GaAs Schottky diodes grown by metal-organic vapor-phase epitaxy (MOVPE) on undoped and Si-doped n-GaAs substrates were determined in the doping range of 2.5 Â 10 15 -1 Â 10 18 cm À3 at low temperatures. The thermionic-emission zero-bias barrier height for current transport decreases rapidly at concentrations greater than 1 Â 10 18 cm À3. The ideality factor also increases very rapidly at higher concentration and at lower temperature. The results agree quite well w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 37 publications
4
80
0
Order By: Relevance
“…6b shows the barrier height as a function of the reverse bias for Ni/4H-SiC SDs at various doping concentrations (reverse I-V data are from several works [5], [6], [21], and [22]). From these figures, we can see two important observations: First, we can see that the barrier height tends to increase with an increase in the donor concentration, while, several authors [28][29][30][31] observed that the barrier height decreases with increasing donor concentration in the case of the forward bias, where the thermionic model is used. Hudait [28] explained this reduction by the barrier height lowering for thermionic field-emission theory, Horváth [29] attributed it to the effect of the interfacial layer and interface states, Noh [30] of his part, attributed this reduction to the Schottky barrier lowering, while, Syrkin [31] explained it by the image force barrier lowering and the value of the surface energy level and the density of surface states.…”
Section: Resultsmentioning
confidence: 81%
“…6b shows the barrier height as a function of the reverse bias for Ni/4H-SiC SDs at various doping concentrations (reverse I-V data are from several works [5], [6], [21], and [22]). From these figures, we can see two important observations: First, we can see that the barrier height tends to increase with an increase in the donor concentration, while, several authors [28][29][30][31] observed that the barrier height decreases with increasing donor concentration in the case of the forward bias, where the thermionic model is used. Hudait [28] explained this reduction by the barrier height lowering for thermionic field-emission theory, Horváth [29] attributed it to the effect of the interfacial layer and interface states, Noh [30] of his part, attributed this reduction to the Schottky barrier lowering, while, Syrkin [31] explained it by the image force barrier lowering and the value of the surface energy level and the density of surface states.…”
Section: Resultsmentioning
confidence: 81%
“…An ideality factor of 1 consequently reflects pure thermionic emission. Should the transport mechanism be more complex and involve both TE and TFE (or other mechanisms), the ideality factor is adjusted to account for tunnelling as described by equation 1, leading to the following equation [22,23]:…”
Section: Resultsmentioning
confidence: 99%
“…The substrates used were p-type Ge (100) wafers, misoriented by 6 degrees towards the nearest (111) plane. The misoriented substrate is vital to produce a double-step surface in order to suppress the formation of APDs at the GaAs/Ge interface [6][7][8]. The MOVPE growth process took place at a pressure of 100 mbar and with a total flow of 14 slpm of palladiumpurified hydrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Large APDs (120 ± 20 nm) are formed at the heterointerface of the sample A due to uncontrolled initial surface nucleation of GaAs epilayer directly onto the Ge substrate [6][7][8][9][10]29]. Using just the As pre-deposition (stage ii) does somewhat reduce the domain size by homogenising the Ge surface with As-As dimers to the order of 21 ± 6 nm [9-10], yet APDs are still significantly present when the low temperature nucleation layer is omitted (stage iii).…”
Section: The Influence Of Various Growth Routines On Apd Self-annihilmentioning
confidence: 99%
See 1 more Smart Citation